Réponses

2014-05-24T11:43:20+02:00
A=3(x+2)-x+1
A= 3x + 6 -x +1
A= 2x + 7

B=-4(-3x-1)-(4x+7)
B= 12x + 4 - 4x - 7
B= 8x - 3

C=-7(-x+3)+3(x+2)+2(x-1)
C= 7x - 21 + 3x + 6 + 2x - 2
C= 12x - 17


A=x(x-5)-2(3+x) sachant que x=1 
A= 1(1-5) -2(3+1)
A= 1*(-4) -2*(4)
A= -4 - 8
A= -12

B=-3x(2x+4)-x(2-3x) sachant que x=1
B= -3*1*(2*1+4) - 1*(2-3*1)
B= -3*(2+4) - 1(2-3)
B= -3*6 - 1*(-1)
B= -18 + 1
B= -17

C=-3(x²+7)+(6x-1)-x(15+7x)-3 sachant que x=1
C= -3(1² + 7) + (6*1-1) - 1(15+7*1)-3
C= -3*9 + 5 -1*22 -3
C= -44